RANCANG BANGUN SISTEM PENGANGGARAN DAN PENGENDALIAN ANGGARAN (STUDI KASUS : UNMUH PONOROGO) - Missa, Bhaga Yanuardo; Widodo, Arifin Puji; Amelia, Tan (Jurnal JSIKA, 2013)
In the budgeting process, the finance department does not know the attributes and estimate nominal for every budget only. During the realization process of the budget plan, it makes UNMUH Ponorogo has lack or excess the budget. Based on the problem, UNMUH Ponorogo needs the budgeting and controlling budget system by taking into key performance indicators (KPI) so that the budget plan can be generated efficiently (not too little or too much) and it can control the budgets. It will determination the attribute and set the standard of costs, makes the work plan and budget plan, handle the budget submission and validation the budget submission, realize the budget and handle the budget accountability. The output from this system is the data attribute and its standard cost, the work plan, budget plan that based on work plan and cost standards of KPI, the comparison report between budget and realization of budget for every department and overall. So from this system, UNMUH Ponorogo can make budget plan based on standard costs in the KPI. In addition, UNMUH Ponorogo can control the budget. Keyword: key performance indikator, budgeting, controlling the budget.